(untitled) (Symposium on Natural and Applied Sciences, 2026)
This scientific article provides a comprehensive analysis of the current implementation of the Law on the State Language of the Republic of Uzbekistan, its legal foundations, and its role in the system of state administration. Additionally, the impact of the state language on societal development is examined from the perspective of socio-political factors. During the research, the effectiveness of the law’s implementation is evaluated based on official statistical data, existing problems are identified, and scientifically based proposals and recommendations for their resolution are developed.